Factors affecting stroke prevention behavior in elderly people with high blood pressure - Thanyarat Phuchongchai; Sumattana Glangkarn; Chaloemporn Namyota (Journal of Education and Health Promotion)
BACKGROUND: Preventing stroke in senior citizens with high blood pressure will reduce disability and mortality rates. The study examined the behaviors and factors influencing stroke prevention behavior in older people. MATERIAL AND METHOD: This cross-sectional study consisted of a sample group of 460 elderly individuals diagnosed with high blood pressure in the Mueang District, Chaiyaphum Province. Data were collected using a questionnaire on stroke knowledge, perception of self-efficacy, including perceived self-efficacy and expected outcome, social support, and stroke prevention behavior. Descriptive statistics and stepwise multiple linear regression analysis were also employed. RESULTS: The overall stroke prevention behavior in older people with high blood pressure was moderate, with a mean score of 3.64 (S.D. = 0.29). Factors influencing stroke prevention behavior in this population sector were high blood pressure, self-efficacy, expected outcomes, and social support from public health personnel, friends, and media. These five factors accounted for 54.2% of the variance in stroke prevention behavior. CONCLUSION: Public health personnel should organize activities or programs to promote behavior change, emphasizing increasing self-efficacy. It is also important to encourage positive expectations for behavior outcomes and foster social support from both media and friends when caring for older people with high blood pressure.